The effects of allowing a second sequential lineup lap on choosing and probative value. - Ruth Horry (Psychology, Public Policy, and Law, 2015)
When presented with a sequential lineup, witnesses see each member of the lineup individually, essentially making a yes/no decision for each person shown. An important policy question is whether witnesses should be allowed to see an additional lap of a sequential lineup. We investigated the impact of a second lap on eyewitness decision-making and on the probative value of suspect identifications. We recruited a large community sample of participants (N = 393), each of whom viewed a target person before seeing a sequential lineup that did or did not include the target. A second lap was either required or optional. The group of participants who accepted the second lap were less able to discriminate between the target and the fillers and responded more conservatively in lap 1 than the group of witnesses who declined the second lap. Responding became more lenient from lap 1 to lap 2. Of the participants who saw a second lap, roughly 40% changed their response, most frequently from a non-identification to an identification. Both culprit identifications and filler identifications increased from lap 1 to lap 2. The probative value of suspect identifications was not significantly different whether witnesses were allowed two laps or one. However, the observed effects may be moderated by a number of system and estimator variables. Further, even small changes in probative value can have very different consequences depending upon the target-absent base rate.